Elotuzumab as a novel anti-myeloma immunotherapy - Sabarinath Venniyil Radhakrishnan; Neelam Bhardwaj; Mary Steinbach; Janet Weidner; Tim Luetkens; Djordje Atanackovic (Taylor & Francis Group, 2017)
Treatment of multiple myeloma has undergone significant change in the last decade with the introduction of new immunomodulatory agents, proteasome inhibitors, and immunotherapeutic approaches. Elotuzumab is a humanized monoclonal antibody targeting CS1, which is a member of the SLAM (Signaling Lymphocyte Activation Molecule) family of proteins, expressed on the surface of myeloma plasma cells. Here we review the preclinical investigations that led to the development of elotuzumab and the clinical studies that resulted in its approval for the treatment of relapsed/refractory multiple myeloma. Although preclinical data looked very promising, elotuzumab monotherapy did not result in objective clinical responses in patients with relapsed/refractory multiple myeloma. However, combination treatment with immunomodulators and proteasome inhibitors resulted in substantial clinical activity in relapsed/refractory MM. Currently, there are several clinical trials ongoing investigating the role of elotuzumab in newly diagnosed myeloma patients and in patients receiving maintenance therapy.